Penyuluhan Mengatasi Keuangan Keluarga Pada Masa Pandemi Covid-19 - Sihotang, Siti Fatimah (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The Covid-19 pandemic that had hit the entire world recently had become an unusual challenge for everyone. This was because this pandemic had changed the activity habits of almost everyone; creating new habits for social distancing. Included getting used to work and study from home. This became a new problem, considering the additional costs that arouse in household finances. As long as many activities were carried out from home, it directly affected the family's financial economy. The economic uncertainty caused by the Covid-19 pandemic in recent months had also resulted in a decrease/loss of household income. Based on the above problems, the purposed of this community service activity was to provide counselling to assist housewives to manage family finances better, during the Covid-19 pandemic. Therefore, precise and careful steps were needed, hence the financial management of the family becomes right on target. One of the efforts that could be done was to carry out Family Financial Management. After the implementation of this community service activity in the form of counselling, the knowledge and understanding of the administrator-members and heads of the Medan HWK (Himpunan Wanita Karya) organization increased. The counselling participants has been able to manage family finances during the Covid-19 pandemic according to the methods. Besides, as the manager of family finances, it is hoped that the administrator-members and heads of the HWK (Himpunan Wanita Karya) women can apply the principles of family financial management with a full sense of diligence and consistency.